Plant productivity, radiation interception and water balance as indicators of tree-crop interactions in hedgerow intercropping systems : a Jatropha - Kikuyu case study - Annandale, John George (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2012.